#Closethegap accelerate post-pandemic recovery through social justice proceedings of the Eighth Annual Public Policy Conference 2022. - Annual Public Policy Conference 2022 Online) (Quezon City Philippine Institute for Development Studies, 2023)
Socioeconomic disparities in the Philippines have persisted and even worsened in the wake of the devastating coronavirus disease 2019 (COVID-19) pandemic. To break longstanding inequities, remove deep-seated structural and systems challenges, and ensure that no one is left behind, social justice should be the front and center of policymaking and program implementation as the country recovers from the socioeconomic crisis brought by the pandemic.

In 2022, the Philippine Institute for Development Studies dedicated the Eighth Annual Public Policy Conference (APPC) to discussing possible policy actions to reduce and remove structural inequities in the post-pandemic era. Through a four-part webinar series, renowned international and local experts and policy analysts from various fields and representatives from the government, academe, private sector, and civil society shared insights on social justice and how it may be effectively applied to the design and delivery of education and health services, social protection programs, and interventions to promote environmental resilience and tackle climate change.

This publication, which compiles the presentations and discussions during the four-part APPC webinar series, is a practical resource for the public and policymakers alike in making informed decisions regarding the post-pandemic future of the Philippines.
"September 2022"--Cover.
Includes bibliographical references.
Keywords: COVID-19 Pandemic, 2020-2023 -- Social aspects -- Philippines -- Congresses; COVID-19 Pandemic, 2020-2023 -- Economic aspects -- Philippines -- Congresses; COVID-19 Pandemic, 2020-2023 -- Government policy -- Philippines -- Congresses; Social justice -- Philippines. -- Congresses; Philippines -- Economic policy; Philippines -- Economic conditions -- 1986- .